Child Access Prevention Laws and Nonfatal Gun Injuries. (1st July 2013) - DeSimone, Jeffrey; Markowitz, Sara; Xu, Jing
Abstract : Many states have passed child access prevention (CAP) laws, which hold the gun owner responsible if a child gains access to a gun that is not securely stored. Previous research on CAP laws has focused exclusively on gun‐related deaths even though most gun injuries are not fatal. We use annual hospital discharge data to investigate whether CAP laws are associated with decreased nonfatal gun injuries. Results from Poisson regressions that control for various hospital, county, and state characteristics, including state‐specific fixed effects and time trends, indicate that CAP laws are associated with reductions in nonfatal gun injuries among children under age 18. Our results are bolstered by the absence of effects on other outcomes such as self‐inflicted gun injuries among adults and nongun self‐inflicted injuries.